Teknologi GPS NEO-6 Untuk Tracking Kapal Penumpang Secara Real Time dengan Fitur Tombol Emergency SOS - Irma Salamah; Nasron Nasron; Dita Azzahra (LPPM STIKI MALANG, 2022)
Monitoring the position of transportation equipment is important in the world of transportation, one of which is on ships. This is needed to know the position of the ship accurately when there is a possible risk of an accident. Global Positioning System (GPS) technology is a satellite navigation system and a geographic positioning system using satellites through 24 satellites that transmit microwave signals to Earth. In this study using the NEO-6M GPS module which functions as a GPS receiver (Global Positioning System Receiver) to detect locations by capturing and processing signals from navigation satellites. The locations that were the target of the test were the Musi River, to be precise, at Location 1 in the Musi 6 area and Location 2 in the Benteng Kuto Besak (BKB) area. Based on location 1 in the Musi 6 area, the Latitude is -3.005045 and the Longitude is 104.751624. Furthermore, for ship testing at location 2 in the BKB area, the results obtained were a Latitude of -2.992315 and a Longitude of 104.760456. The results obtained from this design are able to display information data from ships in the form of Maps on the Blynk application and notifications will appear when the SOS button is pressed. So that it can help the evacuation process when an accident or emergency occurs on the ship correctly and precisely. As well as being able to increase security and a sense of comfort for the safety of ship passengers while using water transportation.